Inclusion of local ecological knowledge within marine protected areas in the Pacific Island region : a thesis submitted in fulfillment of the requirements for the degree of Master of Environmental Management at Massey University of New Zealand - Vaughan-Sanders, Jacqueline-Mary (Massey University, 2020)
Global biodiversity loss and climate change are threatening the survival of marine ecosystems and the Local Ecological Knowledge (LEK) that is inextricably tied to them. Marine Protected Areas (MPAs) are increasingly used worldwide to conserve marine ecosystems and support ecosystem services and cultural values. MPAs are a typically top-down marine management model with the primary aim of biodiversity conservation. The international community and researchers have increasingly recognised the critical importance of including LEK, local communities and Indigenous peoples within MPA decision-making, governance, and management. Despite this, there is a lack of empirical research on the involvement of Indigenous peoples within MPA management and governance. This study addresses this research gap by focusing on how LEK has been included within MPA management in the Pacific Island region. A reflexive thematic analysis is used to examine four publically accessible regional frameworks and action plans pertaining to the management of MPAs in the South Pacific. The results reveal that the inclusion of LEK has been moderately successful within the Pacific Island region through the identification of three themes: i) LEK, livelihoods and biodiversity conservation are interconnected and essential elements within MPAs, ii) LEK is a tool that allows communities to have and regain influence over use of resources through MPA management and governance, and iii) misalignment between regional and international level inclusion of LEK within MPA management. On reflection of these findings, their implications, and how they are situated within the literature, four conclusions and recommendations have been made. First, the focus needs to shift from LEK to LEK holders for meaningful and impactful research on the inclusion of Indigenous peoples and local communities within systematic conservation management. Second, the Pacific Island region needs to improve horizontal alignment across MPA frameworks and actions plans, particularly when stating where regional efforts feed into on the international level. Third, the Pacific Island region should challenge the international community’s weak inclusion of LEK holders within global MPA targets and MPA global standards. Finally, the international community needs to identify the inclusion of LEK and LEK holders as a cross-sectoral objective within all targets and global standards pertaining to MPAs. These amendments will be critical for advancing effective and appropriate MPA management, and empowering and recognising Indigenous rights.
Keywords: 410404 Environmental management